Prevalence and risk factors of gestational diabetes mellitus in Yemen - Ali AD; Mehrass AO; Al-Adhroey AH; Al-Shammakh AA; Amran AA (Dove Medical Press, 2016)
Abdullatif D Ali,1 Amat Al-Khaleq O Mehrass,2 Abdulelah H Al-Adhroey,3 Abdulqawi A Al-Shammakh,1 Adel A Amran4 1Department of Biochemistry, 2Department of Gynecology and Obstetrics, 3Department of Basic Medical Sciences, 4Department of Physiology, Faculty of Medicine and Health Sciences, Thamar University, Dhamar, Yemen Purpose: Gestational diabetes mellitus (GDM) continues to be a significant health disorder triggering harmful complications in pregnant women and fetuses. Our knowledge of GDM epidemiology in Yemen is largely based on very limited data. The aim of this study was, therefore, to determine the prevalence and risk factors of GDM among pregnant women in Dhamar governorate, Yemen.Patients and methods: A total of 311 subjects were randomly selected for this cross sectional survey. Health history data and blood samples were collected using a pretested questionnaire. To determine the prevalence of GDM, the fasting and random blood glucose techniques were applied according to the recommendations of the American Diabetes Association, using alternative methods that are more convenient to the targeted population. Poisson’s regression model incorporating robust sandwich variance was utilized to assess the association of potential risk factors in developing GDM.Results: The prevalence of GDM was found to be 5.1% among the study population. Multivariate analysis confirmed age ≥30 years, previous GDM, family history of diabetes, and history of polycystic ovary syndrome as independent risk factors for GDM prevalence. However, body mass index ≥30 kg/m2 and previous macrosomic baby were found to be dependent risk factors.Conclusion: This study reports new epidemiological information about the prevalence and risk factors of GDM in Yemen. Introduction of proper maternal and neonatal medical care and health education are important in order to save the mother and the baby. Keywords: gestational diabetes mellitus, alternative diagnostic criteria, prevalence risk, Yemen